Analysis of the Use of Online Learning Media on Students’ Achieved Learning Outcomes During the COVID-19 pandemic at SMP PGRI 363 Pondok Petir - Tasia, Fanni Erda; Nurhasanah, Enok; Hamda, Nasmal (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
This research analyses the use of online learning media on the students’ achieved learning outcomes during the COVID-19 pandemic for 8th-grade students at PGRI 363 Pondok Petir. This research applies the descriptive method, which describes and interprets objects as what they are. The data in this research were collected by using observation, interview, and document. The findings of this research show that Google Classroom was used for online media learning for 8th-grade students at SMP PGRI 363. Using Google Classroom resulted in decreased and increased student learning outcomes. The outcome decreased in learning materials; not all students could absorb them. However, there was increasing skill. There is an increase in the skill aspect related to students’ skills in using technology in the field of learning, namely Google Classroom and according to information from teachers, it is stated that students have become more responsible for their learning, where students try to complete the tasks given even without direct supervision from the teacher in class. The results of teacher discussions with student parents during the learning review process using Google Classroom also show that students are becoming increasingly trained to be more independent in managing their learning at home.